Peran Mediasi Tax Knowledge dalam Hubungan Tax Education dan Tax Compliance - Febriani, Eka; Putri, Amanda; Kusumah, Angga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research examines tax education which influences tax knowledge with the mediation of tax knowledge. Data from a survey of 130 individual taxpayers in Samarinda who had taken taxation courses through formal tertiary level education were analyzed using smartPLS, which produces findings that tax education and tax knowledge have a significant and positive effect on tax compliance, tax education has a significant and positive effect on tax knowledge, and tax education has a significant and positive effect on tax compliance through tax knowledge which is partial mediation. This research results in empirical evidence regarding the importance of tax education in increasing tax compliance. High tax compliance will help the government in terms of funding to carry out work programs that can ultimately improve people’s lives.